Matoshree Hospital Management Website: A Comprehensive Platform for Patient Information and Services - Bhandare, Harshada; Lokhande, Isha; Huke, Sakshi; Asabe, Ananya; Patil, Srushti; Tapkire, Mayuri (International Journal of Computer Sciences and Engineering, 2024)
The hospital management website is an essential tool for patients, families, and staff, offering crucial information about available services, appointment scheduling, and departmental contacts. Designed with user-friendliness as a priority, the platform facilitates easy access to important resources, reducing the complexity often associated with healthcare systems. Its organized layout improves communication between the hospital and the community, providing timely updates on services, events, and health initiatives. This level of transparency builds trust, ensuring that patients and their families are well-informed about their healthcare choices. Although the website successfully achieves its goals of accessibility and information dissemination, there are plans for ongoing improvements to enhance the user experience further. Proposed enhancements include the integration of interactive features, better navigation options, and mobile-friendly designs to meet diverse user needs. By continuously evolving, the website aims to strengthen community support and ensure effortless access to critical healthcare information. The website`s focus on essential hospital services and easy patient scheduling ensures a more accessible and efficient healthcare experience for everyone.